2022
DOI: 10.1017/s0272263121000942
|View full text |Cite
|
Sign up to set email alerts
|

Language Experience and Bilingual Children’s Heritage Language Learning

Abstract: Both language input and output are important to child language learners’ heritage language development. Nevertheless, existing studies mainly focus on language input, leaving the significance of language output underexplored. The current study assessed 201 kindergarteners’ Mandarin skills (i.e., receptive vocabulary, receptive grammar, and verbal fluency) in Singapore, and investigated the influence of children’s Mandarin experience, and specifically output, on these Mandarin skills. The results based on multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…In the realm of sentence interpretation, 32 children aged 6 to 12 with HL-Greek in the USA who had used the HL more before age five as well as concurrently did better than peers who had done so less ( Chondrogianni and Schwartz, 2020 ). Sun et al (2022) reported similar findings for 202 4- to 5-year-olds with HL-Mandarin in Singapore. In a very large population study in Spain, Caminal et al (2021) showed that increased parental HL-Catalan proficiency led to parents speaking the HL more often with their firstborn children.…”
Section: Introductionsupporting
confidence: 60%
“…In the realm of sentence interpretation, 32 children aged 6 to 12 with HL-Greek in the USA who had used the HL more before age five as well as concurrently did better than peers who had done so less ( Chondrogianni and Schwartz, 2020 ). Sun et al (2022) reported similar findings for 202 4- to 5-year-olds with HL-Mandarin in Singapore. In a very large population study in Spain, Caminal et al (2021) showed that increased parental HL-Catalan proficiency led to parents speaking the HL more often with their firstborn children.…”
Section: Introductionsupporting
confidence: 60%
“…According to the output hypothesis, other than language exposure, being able to produce the target language actively and getting confirmation or negative feedback from more proficient speakers are vital to learning a second language. A recent study showed that that both home language input and output of the child significantly predicted the home language proficiency in bilingual kindergarteners ( Sun et al, 2022b ). Thus, the relationships between DLLs’ language input and output and oral language proficiency are examined in this present study.…”
Section: Parental Perceptions Of Bilingualism and Home Language Devel...mentioning
confidence: 99%
“…This may reduce communication opportunities for the child, which, while disadvantageous for all children, may be particularly damaging to autistic children, for whom social-emotional relationships may be especially challenging (APA, 2013). The number of places and interlocuters with whom children use a language is a signi cant predictor of their skills in that language (Sun et al, 2022). Access to a heritage language has essential implications for the formation of cultural identity in children (Imbens-Bailey, 1996;…”
Section: Introductionmentioning
confidence: 99%